2021
DOI: 10.1136/thoraxjnl-2021-216885
|View full text |Cite
|
Sign up to set email alerts
|

Bronchoscopic needle-based confocal laser endomicroscopy (nCLE) as a real-time detection tool for peripheral lung cancer

Abstract: IntroductionDiagnosing peripheral lung cancer with the bronchoscope is challenging with near miss of the target lesion as major obstacle. Needle-based confocal laser endomicroscopy (nCLE) enables real-time microscopic tumour visualisation at the needle tip (smart needle).AimTo investigate feasibility and safety of bronchoscopic nCLE imaging of suspected peripheral lung cancer and to assess whether nCLE imaging allows real-time discrimination between malignancy and airway/lung parenchyma.MethodsPatients with su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
45
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 29 publications
(35 reference statements)
0
45
0
1
Order By: Relevance
“…Existing NIR imaging modalities can identify tumor at the macroscopic level, but this study demonstrates microscopic NIR identification of cancer cells in vivo. CLE has been previously studied for endoscopic evaluation of nodules in a variety of organ systems 19 , 25 27 . Prior work in nCLE imaging has relied upon tissue autofluorescence or reverse-contrast imaging in the far-red spectrum after systemic administration of fluorescein 11 , 18 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Existing NIR imaging modalities can identify tumor at the macroscopic level, but this study demonstrates microscopic NIR identification of cancer cells in vivo. CLE has been previously studied for endoscopic evaluation of nodules in a variety of organ systems 19 , 25 27 . Prior work in nCLE imaging has relied upon tissue autofluorescence or reverse-contrast imaging in the far-red spectrum after systemic administration of fluorescein 11 , 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Fiber-based CLE is an adaptation of conventional microendoscopy technology in which a low-power laser illuminates a tissue of interest and transmits light reflected from the tissue via a flexible optical fiber bundle to generate high-resolution tissue images 17 . Both probe-based CLE (pCLE) and needle-based CLE (nCLE) permit autofluorescence imaging as well as reverse-contrast imaging of tissues after systemic administration of fluorescein 11 , 13 , 18 , 19 . Recent studies conducted by Annema and colleagues have shown the benefit of fluorescein-based nCLE as a diagnostic adjunct in the bronchoscopic diagnosis and staging of lung cancer 13 , 19 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To conclude, the study by Kramer et al demonstrates the potential of nCLE imaging technology and will further contribute to the innovative bronchoscopy platforms combining a high tool-in-lesion navigation success and optical endomicroscopy based tissue verification 12. A near microscopy optical biopsy might complement invasive tissue sampling in order to optimise clinical lung nodule management in the near future.…”
mentioning
confidence: 94%
“…In their proof-of-principle study, Kramer et al prospectively demonstrated the feasibility of bronchoscopic nCLE imaging, which aids accurate detection of peripheral pulmonary nodules at the needle tip in a selected patients 12. Good quality nCLE-videos were obtained in 24 out of 26 (92%) patients with suspected peripheral lung cancer (final pathological diagnosis of malignancy in 23 patients).…”
mentioning
confidence: 99%